The role of HMGB1-RAGE axis in migration and invasion of hepatocellular carcinoma cell lines - Chen, Ruo-Chan (Springer US, 2014)
High mobility group protein box1 (HMGB1) and its receptor—receptor for advanced glycation end products (RAGE) are pivotal factors in the development and progression of many types of tumor, but the role of HMGB1-RAGE axis in hepatocellular carcinoma (HCC) especially its effects on metastasis and recurrence remains obscure. Here, we report the role of HMGB1-RAGE axis in the biological behaviors of HCC cell lines and the underlying molecular mechanism. We show that the expressions of HMGB1, RAGE, and extracellular HMGB1 increase consistently according to cell metastasis potentials, while the concentration of soluble form of RAGE (sRAGE) is inversely related to metastasis potential of HCC cells. Furthermore, our data show that rhHMGB1 promotes cellular proliferation, migration, and invasion, and increases the level of nuclear factor kappa B (NF-κB), while administrations of HMGB1-siRNA, RAGE-siRNA, anti-HMGB1 neutralizing antibody, anti-RAGE neutralizing antibody, and sRAGE inhibit cellular proliferation, migration, and invasion. Moreover, we also demonstrate that the expression of NF-кB is inhibited by knockdown of HMGB1 or RAGE. Collectively, these data demonstrate that HMGB1 activates RAGE signaling pathways and induces NF-кB activation to promote cellular proliferation, invasion, and metastasis, in HCC cell lines. Taken together, HMGB1-RAGE axis may become a potential target in HCC therapy.